Interfaces para dispositivos móveis - Santos, Jefferson dos (2013)
Mobile devices have been claimed in recent years as essential accessories for the contemporary man. Hinting as ubiquitous and selling themselves as omnipotent, they constitute a significant portion of the electronic market and computational. Promising to replace the medium and long term personal computers, mobile devices are increasingly invested in features that transform them, sometimes in highly sophisticated equipment and for which the user has to be ready for an efficient use. While participating in a culture of rapid technological change and product obsolescence, mobile devices contribute to the formation of a culture of mobility and portability which tends to accelerate the process of merging the media in a convergence culture. Driven by marketing strategies, the current technological trend is touted as a central element of mobility and the consequent concomitant online connection, as currently conceived more cloud computing or sharing of information, content and interests. Taking this as a panorama skyline trends, this master's research focuses on a research on the concept of mobile devices, their fundamental characteristics as an instrument of the technological era, resource access and manipulation as user and producer, resulting in perspective prosumer set by Alvin Toffler and systematized by Negroponte in view of digital life. Displays the current landscape of numerous devices and their operating structures as well as their means and forms of use, such as human-machine and human prostheses as their coupling to cyberspace in support of everyday life, the laser increasingly fragmented and its growing use and incorporation of the language of games based on the methodology of interface design. From the methodological and technical scope presented applies the concepts developed in a case study of PUCSP, a cultural development of an application for the Android technology that was awarded the Nokia Development, showing its characteristics, stages of development and structuring their interfaces from the perspective of hypermedia language. Concludes in favor of the development work and research scholars who turn to the cultural needs of the population of large cities, in which access to information (within the criteria of mobility) is critical